1996
DOI: 10.1007/bf00170832
|View full text |Cite
|
Sign up to set email alerts
|

Opioid receptor-mediated control of acetylcholine release in human neocortex tissue

Abstract: The effects of various opioid receptor agonists and antagonists on evoked acetylcholine release were studied in slices of human neocortex prelabelled with [3H]-choline, superfused and depolarized electrically (2 rain, 3 Hz, 2 ms, 24 mA) or by K + (20 raM). The 6-opioid receptor agonist DPDPE and the K-opioid receptor agonist U50488 reduced the evoked [3H]-overflow (acetylcholine release) in a concentration-dependent fashion; the cLopioid receptor antagonist naltrindole and the the ~c-opioid receptor antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Because a previous report (Feuerstein et al, 1996b) excludes the involvement of GABA receptors in the ␦-opioid inhibition of ACh release, the findings raise the possibility that ␦ 1 receptor activation selectively affects the release of the cotransmitter somatostatin, although the existence of some "pure" somatostatinergic neurons should not be excluded.…”
Section: A Release Of Acetylcholine Mediated By Opioid Receptorsmentioning
confidence: 74%
See 3 more Smart Citations
“…Because a previous report (Feuerstein et al, 1996b) excludes the involvement of GABA receptors in the ␦-opioid inhibition of ACh release, the findings raise the possibility that ␦ 1 receptor activation selectively affects the release of the cotransmitter somatostatin, although the existence of some "pure" somatostatinergic neurons should not be excluded.…”
Section: A Release Of Acetylcholine Mediated By Opioid Receptorsmentioning
confidence: 74%
“…), very few reports deal with neuropeptide receptors in human CNS. Results from experiments with laboratory animals show that opioids can regulate neurotransmitter release, although with important species differences [see Feuerstein et al (1996b) and references therein]. It is therefore important to investigate the modulation of release by opioids in human brain and, in particular, to characterize the subtypes of opioid receptor involved.…”
Section: Neuropeptide Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Naloxone, an µ-opioid receptor antagonist, antagonized the inhibitory effect of fentanyl on acetylcholine release in the hippocampus (Sakai et al, 2002). However, it has been reported that activation of µ-opioid receptor causes enhancement of acetylcholine release in several brain areas such as the striatum (Green et al, 1976), cortex (Feuerstein et al, 1996), hippocampus (Imperato et al, 1996), and rostral ventrolateral medulla (Taguchi et al, 1999). For example, morphine increased levels of acetylcholine in mouse striatum in a dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%